Changes in protein structure and physicochemical properties of egg white by super critical carbon dioxide treatment. (November 2020) - Ding, Lixian; Zhao, Qiannan; Zhou, Xin; Tang, Chaoqing; Chen, Yujun; Cai, Zhaoxia
Abstract: Supercritical carbon dioxide (SCCD) is a green, novel and practical technology in food processing. In this paper, SCCD treatment was used for enhancing the foaming properties of egg white. The possible mechanism of SCCD pressures increasing the foam ability of egg white protein (EWP) was discussed. The results showed that the maximal foaming capacity (107.7%) was obtained at 9 MPa, which was 3.6 times that of original egg white. Electrostatic force of protein molecules was reduced due to the change of pH value. Meanwhile, the particle size of EWP increased and the absolute zeta potential decreased with SCCD pressure increasing. These changes resulted in an increase of hydrophobicity and viscosity of EWP accordingly. This study found that SCCD treatment caused the exposure of EWP hydrophobic groups through the synergy of high pressure and CO2 solvent. It provided a novel path to improve the foam ability of EWP by physical technology. Highlights: Egg White Samples were treated by supercritical carbon dioxide. Foaming capacity was significantly promoted by SCCD treatment at 9 MPa. Changes in physicochemical properties and protein structures were investigated.